2005
DOI: 10.1080/16501970510040263
|View full text |Cite
|
Sign up to set email alerts
|

ICF linking rules: an update based on lessons learned

Abstract: The newly updated linking rules will allow researchers systematically to link and compare meaningful concepts contained in them. This should prove extremely useful in selecting the most appropriate outcome measures among a number of candidate measures for the applied interventions. Further possible applications are the operationalization of concrete ICF categories using specific measures or the creation of ICF category-based item bankings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
962
0
60

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,110 publications
(1,057 citation statements)
references
References 8 publications
5
962
0
60
Order By: Relevance
“…The ICF distinguishes further between disability (the limitations and restrictions experienced because of a health problem) and quality of life (QoL) (how the person feels about these limitations and restrictions) (11). Measures of QoL provide insight into the subjective experience of illness and disability, taking into account a broad range of areas including perceived health and physical functioning, social relationships, psychological well-being, and environmental support, and their inclusion in routine clinical assessment following amputation has been recommended (12).…”
mentioning
confidence: 99%
“…The ICF distinguishes further between disability (the limitations and restrictions experienced because of a health problem) and quality of life (QoL) (how the person feels about these limitations and restrictions) (11). Measures of QoL provide insight into the subjective experience of illness and disability, taking into account a broad range of areas including perceived health and physical functioning, social relationships, psychological well-being, and environmental support, and their inclusion in routine clinical assessment following amputation has been recommended (12).…”
mentioning
confidence: 99%
“…11 The ICF can be used as a reference for already existing outcome measurements to provide a clear picture of which health domains that are addressed by the different measurements. 12 Reconstructive arm and hand surgery has the potential to improve both passive and active function in the arm and hand in patients with cervical SCI. 13,14 The basis for treatment is the patient's needs and desires as well as the remaining motor and sensory functions in the upper extremities, with no restrictions related to age or time since injury.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with results reported by Faria et al 26 , who observed that the SS-QOL included more distinct categories related to the participation component than did the NHP. Furthermore, two studies of the NHP 27,28 found that most of the concepts measured by this instrument are associated with the body function component and not the participation component. Considering these criteria, if the objective is to evaluate participation based on the use of these instruments and if there is a need to select only one of them, the SS-QOL appears to be more indicated.…”
Section: Discussionmentioning
confidence: 99%